Objective tests and the assessment of the acoustic properties of ear-plugs - Kotarbińska, E.; Kozłowski, E.; Młyński, R. (Archives of Acoustics, 2006)
Ear-plug-type hearing protectors are commonly used in a noisy working environment. In a certification process of ear-plugs only sound attenuation is tested subjectively. There is no requirement of maximum variability in ear-plug insertion loss measured objectively like the requirement of maximum variability in ear-muff insertion loss. The aim of this paper is to present the methodology and the results of insertion loss measurements for ear-plugs. The measurements were carried out in the laboratory test site meeting EN 24869-3 requirements, for test signals consisting of pink noise filtered through one-third octave bands with centre frequencies of 63–8000 Hz, with a newly designed acoustic test fixture. Twenty popular models of ear-plugs (made of foam and cotton wool), with twenty samples of each model, were tested according to the worked out procedure. The mean values of insertion loss and standard deviations for each frequency band of tested ear-plugs are presented.